From “protection” and “preservation” to “development” and “right”: a new approach of objective of shariah via waqf muaqqat - Mohamad, Nor Asiah; Laeba, Muhammad; Hamdan, Omar Mokhtar (2021)
This paper analyses the main objectives of Shariah and its application in waqf. Having acknowledged the priority of the objectives, this paper seeks to expand the scope of the objective with justification to facilitate the ijtihadi basis in ensuring sustainability of waqf. It is argued that a new dimension of protection and preservation of mal as the objective of Shariah is necessary in relevantisation of waqf locally and globally. This paper studies the new dimension of protection and preservation in the perspective of the importance of human development and property rights of waqf practices in Malaysia with special reference to Waqf Muaqqat. The findings show that the employment of ijtihad and fatwa would serve to make waqf stable, flexible and sustainable in developing the legal framework for Waqf Muaqqat in Malaysia.